2012
DOI: 10.1007/s10120-012-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of outpatient chemotherapy with S-1 + cisplatin in patients with advanced gastric cancer

Abstract: Background Regimens of standard-dose cisplatin have usually been administered as inpatient chemotherapy in Japan. This prospective study evaluated the feasibility of outpatient chemotherapy with standard-dose cisplatin in Japanese patients with advanced gastric cancer. Methods Advanced gastric cancer patients received an S-1 ? cisplatin regimen (S-1: 80-120 mg days 1-21; cisplatin: 60 mg/m 2 day 8, every 4-5 weeks), either as outpatient chemotherapy with oral hydration on days 9-10, or as inpatient chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Patients were infused 1000 ml of normal saline before premedication and 1000 ml of normal saline after CDDP administration on day 8. Patients ingest orally 1500 ml of water on day 9 and 10 [8]. Satake et al who is the author in the present study reported that patients were infused 1000 ml of 0.45% NaCl with Mg 2.5 mEq as prehydration and 500 ml of 0.45% NaCl with Mg 2.5 mEq as posthydration with 1000 ml of oral hydration.…”
Section: Discussionmentioning
confidence: 50%
“…Patients were infused 1000 ml of normal saline before premedication and 1000 ml of normal saline after CDDP administration on day 8. Patients ingest orally 1500 ml of water on day 9 and 10 [8]. Satake et al who is the author in the present study reported that patients were infused 1000 ml of 0.45% NaCl with Mg 2.5 mEq as prehydration and 500 ml of 0.45% NaCl with Mg 2.5 mEq as posthydration with 1000 ml of oral hydration.…”
Section: Discussionmentioning
confidence: 50%
“…However, although dehydration is a risk factor for cisplatin-induced AKI, no seasonal variation was observed for AKI cases with cisplatin in JADER ( Supplementary Figure 1 ). In Japan, almost all chemotherapy with standard-dose cisplatin is administered on an inpatient basis with intravenous hydration (Okazaki et al, 2013), while VACV is typically prescribed to outpatients without hydration, and this may have affected the differences of seasonal distribution observed between VACV and cisplatin. Taken together, these findings indicate the importance of increased clinical awareness of VACV-related AKI in the summer months.…”
Section: Discussionmentioning
confidence: 99%
“…Regimens with cisplatin at more than 50 mg/m 2 have usually been administered as inpatient chemotherapy because these are highly emetic and require intensive hydration (24). However, cisplatin is known to be commonly administered as outpatient chemotherapy in other countries.…”
Section: Management Of Chemotherapy In Diverse Patientsmentioning
confidence: 99%